Euroguidelines in Central and Eastern Europe (ECEE) conference and the Warsaw Declaration – a comprehensive meeting report. Issue 5 (24th August 2016) - Kowalska, JD; Oprea, C; de Witt, S; Pozniak, A; Gökengin, D; Youle, M; Lundgren, JD; Horban, A; ,
Abstract : Objectives: The objective of this paper is to summarize the outcomes of the Euroguidelines in Central and Eastern Europe (ECEE) conference held in Warsaw in February 2016. The main aim of this conference was to facilitate a discussion on European AIDS Clinical Society (EACS) guidelines implementation across the region and neighbouring countries and to present the current obstacles in benchmarking HIV care in Europe. Methods: During a 2‐day meeting, there were country‐based presentations using a predefined template so as to make the data comparable and focus the discussion. Areas covered were country epidemiology, surveillance, national strategy for treatment and prevention, standards of care, access to care and treatment availability. Each participant filled in a questionnaire investigating HIV guidelines usage per country. Results: In total, 16 Central and Eastern Europe (CEE) and neighbouring countries were represented at the conference: Albania, Armenia, Belarus, Croatia, Czech Republic, Estonia, Georgia, Hungary, Lithuania, Moldova, Poland, Romania, Russia, Serbia, Slovakia and Turkey. EACS guidelines version 7.1 were used in 14 (87%) countries. In 11 (69%) countries, national guidelines were available, of which eight had been recently updated. Half of the countries declared that they use World Health Organization (WHO) and Department of Health and Human Services (DHHS) guidelines, over one‐third the European Centre for Disease Prevention and Control (ECDC) HIV testing guidelines and one in five the International Antiviral Society−USA (IAS‐USA) Panel guidelines from 2012. Conclusions: Participants declared their will to promote the widespread use of EACS guidelines for HIV infection in the CEE region and neighbouring countries by signing the Warsaw Declaration. They also emphasized the need to increase publishing of data from national cohorts in that region.